The foraging behavior of Diaeretiella rapae (Hymenoptera: Braconidae) on Diuraphis noxia (Hemiptera: Aphididae) - Tazerouni Zahra; Talebi Asghar Ali; Rakhshani Ehsan (Archives of Biological Sciences, 2011)
Host stage preference, functional response and mutual interference of Diaeretiella rapae (McIntosh) (Hymenoptera: Braconidae: Aphidiinae) on Diuraphis noxia (Mordvilko) (Hemiptera: Aphididae) were investigated under defined laboratory conditions (20±1°C; 60±5% relative humidity; 16 h light/8 h dark photoperiod). Nicholson’s model and linear regression were used to determine per capita search-efficiency and the interference coefficient, respectively. There was a significant difference between the rates of parasitism on different stages of D. noxia. The highest parasitism percentage was observed on the third instar nymphs of D. noxia in both choice and no-choice preference tests. Results of logistic regression revealed a type II functional response. The estimated values of search-efficiency (a) and handling time (Th) were 0.072 h-1 and 0.723 h, respectively. The maximum attack rate was calculated to be 33.22. The per capita search-efficiency decreased from 0.011 to 0.004 (h-1) as parasitoid densities increased from 1 to 8. Therefore, different host-parasitoid ratios can affect the efficacy of D. rapae.